Fair food : growing a healthy, sustainable food system for all - Hesterman, Oran B. (PublicAffairs, 2011)
Describes the dysfunctions in the current food system, from chemical runoff to inhumane treatment of animals, and presents new principles and concrete steps to restructure how food is grown, packaged, delivered, marketed, and sold.